Analisis Postur Kerja Operator Dengan Metode RULA dan REBA Di Juragan Konveksi Jakarta - Zeny Fatimah Hunusalela; Surya Perdana; Galuh Krisna Dewanti (IKRAITH-Teknologi, 2022)
Juragan Konveksi is a home industry whose production process is still conventional. Based on the initial observations, there are 3 workstations whose operators often experience injuries, including the pattern cutting station, the sewing process station, and the finishing station. The purpose of this study was to determine the level of work injury on the operator. The methods used are RULA (Rapid Upper Limb Assessment) and REBA (Rapid Entire BodyAssessment). From the results of the NBM (Nordic Body Map) questionnaire calculation, there are four operators who have a high level of risk, namely the pattern cutting process with a score of 80 and 77, and the sewing process with a score of 71 and 73, and two operators have a very high-risk level in the finishing process. with a score of 92 and 103. From the RULA score on the sewing process operator, a score of 6 was obtained, which means that further investigation is needed, and changes must be made immediately. Then for the REBA score on the pattern cutting and finishing process operators get a value of 8 and 10 which means there is a high risk of injury/muscle disorders. This means that it is necessary to make improvements to the productionprocess to reduce work injuries for operators.